Sea spiders (Arthropoda: Pycnogonida) collected during the Madibenthos Expedition from Martinique shallow waters - Sabroux, Romain; Hassanin, Alexandre; Corbari, Laure (European Journal of Taxonomy, 2022)
This study presents the inventory of sea spiders (Pycnogonida) sampled during the Madibenthos Expedition in Martinique (West Indies). Species were discriminated leaning on morphological and molecular data. A total of 761 specimens are classified in 72 species, 16 genera and nine families. Thirteen new species are described: Ammothella dirbergi sp. nov., A. krappi sp. nov., Tanystylum boucheti sp. nov., T. ingrallis sp. nov., Ascorhynchus iguanarum sp. nov., Eurycyde kaiouti sp. nov., Nymphon dorlis sp. nov., N. ludovici sp. nov., N. martinicum sp. nov., N. timons sp. nov., Anoplodactylus madibenthos sp. nov., Pycnogonum cesairei sp. nov. and Rhynchothorax sidereus sp. nov. We describe a neotype for Anoplodactylus micros Bourdillon, 1955 from the type locality. Martinique now includes 79 species of sea spiders, mostly endemic to the Tropical Northwestern Atlantic, cosmopolitan or shared with the South America Atlantic coast. Some species are potentially introduced. However, our knowledge of the distribution of species found in Martinique is probably biased by the scarcity of diagnostic morphological characters. Also, nine potentially cryptic species (discriminated on genetic data alone), are identified, shedding light on the overlooked diversity of sea spiders in the Tropical Northwestern Atlantic. Therefore, we call for a more widespread use of barcoding in sea spiders.